Fiscal incentives in Nigeria : lessons of experience - Central Bank of Nigeria, Research Department; Central Bank of Nigeria (Abuja, Nigeria Central Bank of Nigeria, 2013)
Analyzes fiscal incentives in Nigeria drawing lessons from experience emerging as well as developing economies.
Includes bibliographical references.
oif 16/05/17
Ref.
Keywords: Fiscal policy; Nigeria